Love in the time of cholera - Garcia Marquez, Gabriel, 1928- (London: Penguin Books, 2007)
A love story that ranges from the late nineteenth century to the early decades of the twentieth, tracing the lives of three people and their entwined fates.
Translation of: El amor en los tiempos del colera.
Adult.
Adult
Keywords: Man-woman relationships -- Fiction; Love stories; Man-woman relationship -- Fiction; Colombia -- Fiction; Colombia -- Fiction; Love stories